The Electrocortical Signature of Successful and Unsuccessful Deception in a Face-to-Face Social Interaction - Wagner-Altendorf, Tobias A.; van der Lugt, Arie H.; Banfield, Jane F.; Meyer, Carsten; Rohrbach, Caterina; Heldmann, Marcus; Münte, Thomas F. (Frontiers in Human Neuroscience, 2020)
Deceptive behavior, and the evaluation of others’ behavior as truthful or deceptive, are crucial aspects of human social interaction. We report a study investigating two participants in a social interaction, performing a deception task. The first participant, the “informant”, made true or false autobiographical statements. The second participant, the “detective”, then classified these statements as truth or lie. Behavioral data showed that detectives performed slightly above chance, and were better at correctly identifying true as compared with deceptive statements. This presumably reflects the “truth bias”: the finding that individuals are more likely to classify others’ statements truthful than as deceptive – even when informed that a lie is as likely to be told as the truth. EEG was recorded from the informant. Event-related potential (ERP) analysis revealed a smaller contingent negative variation (CNV) preceding “convincing” statements (statements classified as true by the detective) compared to “unconvincing” statements (statements classified as lie by the detective) – irrespective of whether the statements were actually truthful or deceptive. This finding suggests a distinct electrocortical signature of “successful” compared to “unsuccessful” deceptive statements. One possible explanation is that the pronounced CNV indicates the individuals’ higher “cognitive load” when processing unconvincing statements.